The research methodology for malnutrition risk identification and dietary practices among community living elderly - Hamirudin, Aliza Haslinda; A. Rahman, Nor Azlina; Sidek, Suriati; Zainudin, Norain (IIUM Press, 2016)
Introduction: Nutrition screening is an initial procedure to identify malnutrition, whilst subsequent nutrition intervention is warranted for at risk individuals. However, none of nutrition screening studies conducted among Malaysian elderly accompanied by individualized nutrition intervention. The objective here is to describe the methodology to determine malnutrition risk and nutritional status of elderly in community at baseline and after 3 months of nutrition intervention; and to assess perception of elderly on their dietary practices.